Endogenous 2μ Plasmid Editing for Pathway Engineering in Saccharomyces cerevisiae - Zeng, Bo-Xuan; Yao, Ming-Dong; Xiao, Wen-Hai; Luo, Yun-Zi; Wang, Ying; Yuan, Ying-Jin (Frontiers in Microbiology, 2021)
In Saccharomyces cerevisiae, conventional 2μ-plasimd based plasmid (pC2μ, such as pRS425) have been widely adopted in pathway engineering for multi-copy overexpression of key genes. However, the loss of partition and copy number control elements of yeast endogenous 2μ plasmid (pE2μ) brings the issues concerning plasmid stability and copy number of pC2μ, especially in long-term fermentation. In this study, we developed a method based on CRISPR/Cas9 to edit pE2μ and built the pE2μ multi-copy system by insertion of the target DNA element and elimination of the original pE2μ plasmid. The resulting plasmid pE2μRAF1 and pE2μREP2 demonstrated higher copy number and slower loss rate than a pC2μ control plasmid pRS425RK, when carrying the same target gene. Then, moving the essential gene TPI1 (encoding triose phosphate isomerase) from chromosome to pE2μRAF1 could increase the plasmid viability to nearly 100% and further increase the plasmid copy number by 73.95%. The expression using pE2μ multi-copy system demonstrated much smaller cell-to-cell variation comparing with pC2μ multi-copy system. With auxotrophic complementation of TPI1, the resulting plasmid pE2μRT could undergo cultivation of 90 generations under non-selective conditions without loss. Applying pE2μ multi-copy system for dihydroartemisinic acid (DHAA) biosynthesis, the production of DHAA was increased to 620.9 mg/L at shake-flask level in non-selective rich medium. This titer was 4.73-folds of the strain constructed based on pC2μ due to the more stable pE2μ plasmid system and with higher plasmid copy number. This study provides an improved expression system in yeast, and set a promising platform to construct biosynthesis pathway for valuable products.